Morphological characterisation of a new and two known species of Ditylenchus Filipjev, 1936 (Nematoda: Anguinidae) from Iran - Karani, Hossein Mirbabaei; Eskandari, Ali; Ghaderi, Reza; Heydari, Ramin; Miraeez, Esmaeil (Zootaxa, 2017)
Ditylenchus sturhani sp. n. from the rhizosphere of grasses in East Azarbaijan province, Northwestern Iran, is described and illustrated. The new species is characterised by a straight to slightly arcuate body 656-865 µm in length, presence of four incisures in each lateral field, slender stylet 10–12 µm in length, pharyngeal basal bulb offset or slightly overlapping the intestine, post-uterine sac 1.0–1.9 vulval body diameter long and conical tail with finely rounded terminus. Differences with closely related species including D. solani, D. ausafi, D. angustus, D. dipsaci, D. drepanocercus, D. obesus and D. gallaeformans are discussed. In addition, Iranian populations of two known species, D. valveus and D. virtudesae, are morphologically characterised.